(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2024)
The Palace of Baron d’Erlanger in Sidi Bou Saïd in Tunisia received special attention during the nineties, and a daring restoration project was launched in 1992, this presentation will seek to present this pilot project to safeguard this illustrious building which could be taken as a model. We will insist on heritage recognition, the aspect of protection, the restoration project with its operational concepts such as conservation, critical intervention, innovation and enhancement. This project benefited from a series of favourable circumstances, a recognition of the heritage value, which is not always the case especially for the colonial heritage, a strong political will, a large and available budget, a young institution with flexible management, accompetent team with clear ideas, the carrying out of the necessary studies by specialist service providers and work by competent companies. This pilot project unfortunately remained a unique project and failed to convert into a strategy for the conservation and restoration of historic monuments in Tunisia, despite the measure which was taken within the framework of legislation and training, but the practice did not follow. keywords: Critical Restoration, Baron d’Erlanger Palace, Tunisian Colonial Heritage